Екологічна криза як криза існуючої системи цінностей - Хилько, Микола Іванович; Khylko, Mykola I.; Хилько, М. І. (Одеса, 2019)
З’ясовано, що сучасна екологічна криза має глибокі соціально-економічні корені але, головним чином це криза духовності. Ідея всеосяжного контролю над природою є плодом зарозумілості і невиправданої засміченості свідомості хибними ідеями, що природа існує лише для комфорту людини. Виявлено одну з найістотніших суперечностей, що значною мірою виражає сутність екологічної проблеми - суперечність між економічним поступом людства і можливостями біосфери до самовідновлення. Зазначається, що стратегія практичних орієнтацій призвела до споживацтва, виснаження природних ресурсів і деградації природи. Акцентується увага на особливій небезпеці явища споживацтва як: з економічної точки зору, оскільки природа не в змозі через обмеженість її ресурсів у кожний даний момент часу задовольнити нескінченні матеріальні потреби людини; з геополітичної посилюється агресивність поведінки людей, народів і держав в умовах обмежених ресурсів; з моральної - оскільки націленість на споживацтво так званих модних, престижних речей будь за веде до втрати. людиною розуміння цінності і цілісності природи, і як наслідок викривлене став лення до самої себе як особистості. Для такої людини чистота повітря, води, ґрунтіві лісів перестає бути цінністю, оскільки головними стають статок, престиж, гроші, інші подібні приваби. У цьому сенс примітивного споживацького підходу до життя і природи. Робиться висновок, що обмеженість сучасного людства в ресурсах - це результат дії певних соціальних і культурних чинників, на які можна впливати через органі зацію суспільного життя. Вищі духовні цінності повинні якось регулюв ати побутові потреби та їх диференціацію. Потрібне нове переосмислення місця людини у світобудові: розглядати людину не як завойовника природи, а як органічну її складову частину, тобто докорінно змінити цінності, насамперед ті, які регулюють ставлення людини до природи. Важливо усвідомити, що саме по собі зростання добробуту, поліпшення умов існування ще не робить людей щасливими. Сучасній людині потрібно вгамувати свої традиційні раціонально-прагматичні пріоритети, суттєво підвищити рівень моральності й духовності, усвідомити, що в процесі природокористування здобувається не тільки «хліб насущний», а й «хліб духовний». Пропонуються основні напрями зміни вектору економічного розвитку, так звані стратегічні екологічні ініціативи людства, які водночас були б основою зміни моральної парадигми розвитку в якій економічним вважалося б тільки те, що є екологічним.

It has been discovered, that the current ecological crisis has far-reaching social-economic roots, even though it is mainly caused by the crisis of spirituality. The idea of allencompassing control over nature is a fruit of arrogance and the result of the mind being polluted by an amiss idea that nature exists solely to provide comfort to man. The research identified one of the most significant contradictions, which, for the most part, defines the essence of the environmental issue – the contradiction between the economic progress of mankind and the regeneration capabilities of the biosphere. It has been stated that the p ractical orientation strategy has led to consumerism, depletion of natural resources and the overall natural degradation. Attention is drawn to the particular danger brought upon by the phenomenon of consumerism, such as: in economic terms it is viewed as dangerous because, due to being limited in resources, nature is incapable of fulfilling endless material needs of mankind in any given moment; in geopolitical terms it causes increasingly aggressive behaviour in people, nations and countries in circumstances of limited resources; in moral terms it is due to the fact that focusing on being a fashionable and prestigious consumer leads to a person losing the understanding of the importance of the integrity of nature, and, as a result, gaining a distorted perception of oneself, as a person. For people like that clean air, water, soil and forests lose any significance, because their main values are – wealth, prestige, money and other similar amenities of the material world. This is the essence of the primitive consumeristic approach to life and nature. The research draws a conclusion that the contemporary resource limitations of mankind are caused by the influence of certain social and cultural factors that can be affected by how the public life is organized. Lofty spiritual values should somehow regulate the daily living necessities and their differentiation. Humanity needs to rethink their place in the world structure in order to view a man not as the conqueror of nature, but rather as an organic part of its structure, which would, of course, mean radically changing the values, particularly those concerning the attitude toward nature. It is crucial to realize that the increase of welfare and living conditions on its own doesn’t make people happy. Modern mankind needs to review their traditional rational-pragmatic priorities, fundamentally increase the levels of morality and spirituality, and realize that in the process of using natural resources people are to gain not only the “daily bread” for our bodies, but also the “bread” for our souls. The research paper provides suggestions on the main changes to the vector of economic development, the so-called strategic environmental initiatives of humanity, that would at the same time become the bases for the shift of the moral paradigm of the mankind development, in which only the ecologically rational things would be considered economically rational.
Хилько М. І. Екологічна криза як криза існуючої системи цінностей / М. І. Хилько // S.P.A.C.E. Society, Politics, Administration in Central Europe : електронний науково-практичний журнал / редкол.: Д. Маршалек-Кава (голов. ред.), Д. В. Яковлев (відп. ред.) ; НУ «ОЮА». – Одеса, 2019. – Вип. 10. – С. 3-13. DOI: 10.32837/2519 8858/10/129
Keywords: екологічні цінності; екологічна криза; біосфера; споживацтво, природні ресурси; стратегічні екологічні ініціативи; ecological values; ecological values; biosphere; consumerism; natural resources; strategic environmental initiat ives; Research Subject Categories::NATURAL SCIENCES::Earth sciences::Atmosphere and hydrosphere sciences::Climatology